Acute rheumatic fever and rheumatic heart disease in the Kimberley: using hospitalisation data to find cases and describe trends. (28th August 2014) - Murdoch, Jacqueline; Davis, Stephanie; Forrester, Janice; Masuda, Lynette; Reeve, Carole
Abstract Objective: To describe the epidemiology of hospitalisations due to acute rheumatic fever (ARF) and rheumatic heart disease (RHD) in the Kimberley region of Western Australia (WA) and use these data to improve completeness of the WA RHD Register. Methods: Retrospective analysis of Kimberley regional hospitalisation data for hospitalisations coded as ARF/RHD from 01/07/2002 to 30/06/2012, with individual follow‐up of those not on the register. Annual age‐standardised hospitalisation rates were calculated to determine hospitalisation trend. Results: There were 250 admissions among 193 individuals. Of these, 53 individuals (27%) with confirmed or probable ARF/RHD were not on the register. Males were less likely to be on the register (62% versus 79% of females, p<0.01), as were those hospitalised with ARF without heart involvement (68% versus 87% of other ARF diagnoses, p<0.01). ARF/RHD hospitalisation rates decreased by 8.8% per year (p<0.001, rate ratio = 0.91, 95%CI 0.87–0.96). Conclusions and implications: Using hospitalisation data is an effective method of identifying cases of ARF/RHD not currently on the register. This process could be undertaken for initial case finding in areas with newly established registers, or as regular quality assurance in areas with established register‐based programs. Reasons for the observed decrease in hospitalisation rates remain unclear and warrant further investigation.